The Effects of Growth Opportunity and Company Size on the Financial Performance of Islamic Commercial Banks through Capital Structure - Widy Aulia Rahma; Layaman Layaman; Diana Djuwita (Fakultas Ekonomi dan Bisni Islam UIN Siber Syekh Nurjati Cirebon, 2026)
This study aims to determine the effect of growth opportunity and company size on financial performance, with capital structure as a mediating variable, in Islamic commercial banks in Indonesia for the period 2019-2025. The research method used is quantitative associative analysis, using secondary data with purposive sampling techniques and 48 samples. Data analysis used path analysis with EViews to test the hypotheses. The results show that growth opportunity and company size have no effect on financial performance, while growth opportunity has a positive effect on capital structure. Financial performance has a negative effect on capital structure. Capital structure has no effect on financial performance and is unable to mediate the relationship between the variables. This research is important for understanding the internal factors that influence the financial performance of Islamic banks following the COVID-19 pandemic growth slowdown to encourage efficient capital use and achieve better profits.